Microwave-Assisted Extraction’s Kinetics of Phycobiliprotein from Spirulina Platensis: Influence of Citric Acid Concentration - Pamungkas, Kevin Dyo; Karyadi, Joko Nugroho Wahyu; Setyaningsih, Widiastuti; Susanti, Devi Yuni (Trends in Sciences, 2025)
Phycobiliproteins (PBP), such as phycocyanin (PC), allophycocyanin (APC), and phycoerythrin (PE), are photosynthetic pigments in Spirulina platensis with antioxidant potential for food and medicine. This study optimized microwave-assisted extraction (MAE) of PBP with citric acid (1, 2, and 3 %) as a green solvent to enhance yield and stability using kinetic approach. MAE increased solvent temperature from 30 to 60 °C, accelerating PBP release while preserving its bioactivity. Three kinetic models, Peleg, pseudo-first order (PFO), and pseudo-second order (PSO), were applied to analyze extraction kinetics. Peleg effectively described the initial phase, indicating that higher CA concentrations enhanced PBP release. PFO captured the diffusion-driven phase, while PSO provided the most accurate equilibrium prediction by considering adsorption and solvent-protein interactions. Among the models, PSO showed the highest extraction capacity (Ce = 4.45 × 10⁻² mg/mL at 3 % CA), best R² (≥ 0.99), and lowest MAPE (3.45 %), confirming its superior fit at equilibrium. These findings highlight PSO as the best model for predicting maximum extraction, while Peleg and PFO remain relevant for the early and middle phases. The study confirms MAE with citric acid as an efficient, sustainable method for PBP extraction from Spirulina platensis. HIGHLIGHTS MAE improves phycobiliprotein yield from Spirulina platensis. The addition of citric acid in solvent increases the extraction rate and capacity. Citric acid prevents phycobiliprotein degradation by controlling pH and oxidation. Kinetic models evaluate the influence of citric acid on extraction and stability. Peleg, PFO, and PSO models effectively describe the dynamics of PBP extraction. GRAPHICAL ABSTRACT